Proposed Business Strategy to Increase Competitiveness in Audio Design Industry (Case Study : Ugly Ghost Record) - Simon, Zefanya Ferdinand; Wandebori, Harimukti (Universitas Pamulang, 2025)
Audio design businesses have seen considerable expansion, driven by sustained demand in the film production, advertising, and digital content sectors. The size of the worldwide post-production audio market is projected to grow to 46,5 million in 2031 from 22 million in 2021. The creative economy market, to which the audio design business belongs, has seen substantial growth with an estimated growth of approximately 8% until 2029. Ugly Ghost Record is an independent design sound studio specializing in the film and advertising industry. Despite having a good reputation among the creative community, the company faced a series of challenges in maintaining its competitiveness. Ugly Ghost Record recorded a decline in sales by -67% from 2022 to 2024. The decline was caused by the dependence on limited projects, the lack of clear targets, and the lack of business strategies leading to instability in revenue. The aim of this study is to analyze internal and external factors affecting Ugly Ghost Record, identify elements that impact the company's competitive power, and design business strategies capable of strengthening the company's profitability and sustainability. The research methodology adopted involves internal and external analysis through the use of tools such as the VRIO Framework, Value Chain Analysis, PESTEL Analysis, Porter's Five Forces, and competitor analysis. The findings of these analyses will be synthesized using the application of SWOT and TOWS Matrix to generate appropriate strategies. This research aims to provide useful knowledge to Ugly Ghost Record and other independent audio design studios to create more adaptive and competitive business strategies amidst the continuous evolution of the industry.